THERMAL DECOMPOSITION REACTION KINETICS MODEL OF POWDERED BASTNAESITE - Tu G.F.; Zhang S.R.; Ren C.Z.; Xing P.F.; Zhang C.X. (My University, 2000)
The thermal decomposition procedure of powdered bastnaesite from Mianning was investigated, and TG-DTA curves of bastnaesite were tested in atmosphere. According to the model provided by Criado, the kinetics data were calculated and treated with thermal analysis techniques, and kinetics curves of thermal decomposition reaction of powdered bastnaesite were drawn. Comparing these curves with the standard curves and combining with the previous research results of kinetics parameter calculation, the results confirmed that the reaction mechanism was nucleation and nuclei growth, and its differential and integral forms of reaction kinetics model can be expressed as: f (α) - (1 - α) and g (α) - -ln(1 - α) respectively.